New length–weight relationships and Lmax values for fishes from the Southeastern Mediterranean Sea. (20th August 2012) - Edelist, D.
Summary Length–weight relationships (LWR) of fish serve as building blocks in ichthyology and fishery science. In this study LWR knowledge is extended to some species, regions and sizes of fish either incomplete or missing from the literature or from the online databank (FishBase). For several species data are presented for the first time, while other entries are improved and expanded. Organisms were captured by trawl from the continental shelf of the Israeli coast, where fishes were hypothesized as being small due to low productivity and high water temperatures – a phenomenon called 'Levantine Nanism'. Despite this, for nine of the 43 species presented here the maximum length values exceeded their Lmax in FishBase. The dominance of fishes of Indo‐Pacific origin among the species with exceptionally large specimens (7 of 9) is in agreement with Bergmann's rule; it is thus hypothesized here that these large specimens result from the low temperatures in the Mediterranean compared to their warm Indo‐Pacific sources. This is an example of the superb adaptation of tropical species to the Mediterranean and suggests that Levantine Nanism may be limited to indigenous species.